(untitled) (Semiárida, 2021)
To carry out largescale ecological restoration projects, for example through direct seeding or outplantings, it is necessary to have large quantities of seeds able to germinate. A major obstacle in drylands is that a high percentage of species have seeds with dormancy. Particularly in arid zones, 80 % or more of native shrub species have seeds that do not germinate without breaking dormancy, so without knowledge of effective germination treatments, the possibilities of applying the aforementioned seeding and planting techniques are extremely limited. An additional problem in some species is the difficulty that arises in the extraction of the seeds of the fruit (particularly in large scales) as occurs in species of Larrea genus. In this work, the results of the evaluation of three treatments on fruits and seeds of Larrea cuneifolia Cav. were presented. Two alternatives consisted of soaking the fruits and produced low germination percentages (32.67 % and 35.67 %), without significant differences with the control. In contrast, a sandpaper system powered by an electric drill provided a value of 61.33 % of germinated seeds. In this last treatment, the lowest mean germination time (8.60 days) and the lowest germination initiation index (2.40 days) were also recorded. The results obtained with the sandpaper system constitute a first advance towards the development of lowcost technologies, applicable to large quantities of fruits and / or seeds, accessible for use in rural populations in the fight against ecological and social effects caused by the desertification.